(untitled) (Journal of Pakistan Orthopaedic Association, 2019)
Objective: To determine the short term functional and radiological results of open reduction of Developmental Dysplasia of Hip (DDH) through anterolateral approach. Methods: This was a descriptive study conducted in Paediatric unit of Orthopaedic department, Khyber teaching hospital, Peshawar from January 2018 to December 2018.Children with DDH fulfilling the inclusion criteria were treated with open reduction via anterolateral approach. Post-operative clinical outcome was assessed with Mckay’s criteria while radiographic outcome was assessed by measuring Acetabular index, neck shaft angle and restoration of Shenton line and concentric reduction. Results: Total patients were 35(age more than 18 months).Male were 9(25.7%) while female were 26(74.3%). Mean age was 3.1 ± 1.71 years. Family history of DDH was positive in 06 cases (17.1%). According to Mckay’s criteria 20(57.1%) patients had excellent functional outcome, 8(22.8%) had good, 2(5.7%) fair and 5(14.2%) patients had poor results. Mean Pre-operative Acetabular index (AI) was improved from 35.70 ± 5.830 to post-operative 22.50 ± 5.60. Concentric reduction were found in 34(97.1%) patients and subluxation in one (2.8%) patient. About 6(17.1%) patients had femoral head avascular necrosis (AVN). Mean follow up period was 18 months. Conclusion: Anterolateral approach of hip for open reduction is an excellent approach as it gives better functional and radiological outcome in neglected Developmental Dysplasia of Hip (DDH).